Karakter Tokoh Utama dalam Novel Suara Samudra Karya Maria Matildis Banda Kajian Psikoanalisis Sigmund Freud - Evrasia Kristina Timbu; Marselus Robot; Margareta P.E Djokaho (Lembaga Yasin AlSys, 2026)
The characterization of the main character is an important element in literary works because it represents personality dynamics that develop through conflicts and life experiences. This study aims to analyze the character of Arakian as the main character in Maria Matildis Banda’s novel Suara Samudra based on Sigmund Freud’s theory of personality structure. This study employed a qualitative descriptive method with a psychoanalytic approach focusing on three elements of personality: the id, ego, and superego. The findings show that the ego is the most dominant element of Arakian’s personality. This ego dominance indicates that Arakian is rational, logical, and thoughtful in confronting various conflicts and realities of life. Arakian is also portrayed as a strong and resilient individual with a high degree of self-control and the ability to adapt to harsh realities of life. This study concludes that ego dominance plays an important role in shaping Arakian’s ability to control his internal impulses and adjust his actions to the realities he faces. These findings contribute to the development of literary psychology studies, particularly in understanding character formation from the perspective of Sigmund Freud’s psychoanalysis.